Osteoarthritis Depressive, Loneliness and Social Isolation in Later Life and the Robotic Companion - Ray, Marks (Journal of Aging Research And Healthcare, 2025)
Background Older adults with disabling osteoarthritis may be severely impacted by negative emotions and pain, especially if they feel isolated. Review Aims 1) To summarize the research base concerning the presence of depression in older adults suffering from osteoarthritis; 2) To examine the degree to which mitigating loneliness is desirable in this regard and may be helped by one of the many emergent robotic social devices offering companionship; and 3) To provide directives for professionals who work or are likely to work with this population in the future. Methods Reviewed were current publications detailing some aspect of osteoarthritis in the older adult, depression, emergent loneliness and social isolation, and the role and impact of robotic personal ‘friends’ in this realm. Results Collectively, these data reveal efforts to reduce and mitigate different degrees of depression in older adult osteoarthritis cases are needed and that social robots may help quell isolation. Implication Those older adults with osteoarthritis suffering from depression and emergent loneliness and social isolation may benefit from robotic human or pet like contacts and interactions regardless of cause and overall health status, but the key is still loneliness prevention.
Keywords: Depression; Loneliness; Older Adults; Osteoarthritis; Robotic Pets; Social Robots